Making isometric social real-time games with HTML5, CSS3, and Javascript - Pagella, Mario Andrés (O'Reilly, 2011)
Anyone familiar with Zynga's Farmville understands how fun and addictive real-time social games can be. This hands-on guide shows you how to design and build one of these games from start to finish, with nothing but open source tools. You'll learn how to render graphics, animate with sprites, add sound, validate scores to prevent cheating, and more, using detailed examples and code samples. By the end of the book, you'll complete a project called Tourist Resort that combines all of the techniques you've learned. You'll also learn how to integrate your game with Facebook. If you're familiar with.